2018
DOI: 10.1080/14767058.2018.1481037
|View full text |Cite
|
Sign up to set email alerts
|

Diet and exercise for preeclampsia prevention in overweight and obese pregnant women: systematic review and meta-analysis

Abstract: Diet and exercise in overweight or obese pregnant women are beneficial in reducing gestational weight gain. However, these interventions do not reduce the risk of PE or hypertensive disorders of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 44 publications
3
38
0
4
Order By: Relevance
“…13 However, this result is consistent with prior findings of lifestyle intervention in pregnancy which demonstrate a reduced risk for GDM but not preeclampsia. 19,20 These results are also consistent with a study by Sweeting et al, which found a high rate of HDP (26.3%) in women with GDM onset before 12 weeks of gestation and borderline hemoglobin A1c (mean AE SD, 5.7% AE 1.3) despite intervention (diet, exercise, monitoring, AE insulin as indicated). 21 However, these results somewhat contrast a recent subgroup analysis of the lifestyle in pregnancy (LiP) study by Vinter et al 22 and a recent feasibility study by Hughes et al 15 Specifically, Vinter et al assessed a subgroup of women from the LiP study with early-onset GDM.…”
Section: Discussionsupporting
confidence: 91%
“…13 However, this result is consistent with prior findings of lifestyle intervention in pregnancy which demonstrate a reduced risk for GDM but not preeclampsia. 19,20 These results are also consistent with a study by Sweeting et al, which found a high rate of HDP (26.3%) in women with GDM onset before 12 weeks of gestation and borderline hemoglobin A1c (mean AE SD, 5.7% AE 1.3) despite intervention (diet, exercise, monitoring, AE insulin as indicated). 21 However, these results somewhat contrast a recent subgroup analysis of the lifestyle in pregnancy (LiP) study by Vinter et al 22 and a recent feasibility study by Hughes et al 15 Specifically, Vinter et al assessed a subgroup of women from the LiP study with early-onset GDM.…”
Section: Discussionsupporting
confidence: 91%
“…The title and abstract of a subset of 265 citations were double screened, with over 98% agreement. Of the 75 full text articles screened, 16 (covering 15 separate reviews) were included 12,26–40 . Table S3 provides reasons for exclusion at full text.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of reviews only included RCTs of women with overweight or obesity prior to pregnancy or when booking for antenatal care 27–34,36,37,40 . The other four reviews incorporated women of all BMIs but providing subgroup analysis for women with overweight or obesity 12,26,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…This Journal alone has published 8 articles in the past 2 years related to the topic of obesity or excessive gestational weight gain 1‐8 . There were 9 systematic reviews on the topic, limited to maternal and early infant effects, in 2019 9‐17 . However, what is frequently left out of studies, especially intervention studies, are any outcomes that pregnant women themselves may care about or that are now commonly called patient‐reported outcomes.…”
Section: Dadouch R Hall C Du Mont J D'souza R Obesity In Pregnancmentioning
confidence: 99%